Perancangan Pembuatan E-Learning Berbasis Website Pada SMK Ad-Da’wah Jakarta - Sepitri Daruyani; Irawaty Irawaty; Rr. Artiana Krestianti; Orita Dwi Purbiyanti; Rifky Rahman Hakim (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
In the world of education, there are many elements that can affect the achievement of learning outcomes, including elements of teachers, students, curriculum and facilities and infrastructure that can support learning. Currently, there are still many students in learning who have not found the answer on their own because they are not given the opportunity to practice by the teacher, thus making students feel bored and more passive. Currently, there are still many schools whose students are only given memorization about concepts and not understanding and mastering concepts in terms of solving a problem plus the support of teachers who are less creative in using media in the learning process which makes it increasingly difficult for students to understand the material. Learning methods that take place effectively and efficiently and can be done anytime, anywhere, using any path and with any access speed can be done with the E-learning method. The E-learning method, apart from being able to provide teaching materials and instruction in learning that can be accessed anytime and anywhere, also does not require a large room like a conventional room. In the teaching and learning process there are several problems that arise, namely the problem of limited learning time at AD-DA'WAH Vocational School, the lack of interaction between teachers and teachers outside school hours, limitations between classrooms and the number of students who are not commensurate, which makes the learning process less efficiency. These problems will be solved by designing a learning application with e-learning, which is proven to be efficient in solving problems such as those that occur in the teaching and learning process. The results showed that the e-learning method succeeded in increasing positive efficiency when applied to solve problems. Making e-learning using PHP, MySql, OOP, jQuery, Ajax, CSS as programming languages.